2015
DOI: 10.1080/10986065.2015.1016811
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude Representations and Counting Skills in Preschool Children

Abstract: When children learn to count, they map newly acquired symbolic representations of number onto preexisting nonsymbolic representations. The nature and timing of this mapping is currently unclear. Some researchers have suggested this mapping process helps children understand the cardinal principle of counting, while other evidence suggests that this mapping only occurs once children have cardinality understanding. One difficulty with the current literature is that studies have employed tasks that only indirectly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Fuhs, Nesbitt, & O'Rear 591 vanMarle, Chu, Li, and Geary (2014) used a battery of symbolic math tasks and found that it was children's cardinality knowledge that mediated the link between ANS task performance and math achievement, suggesting that children's ANS acuity influences symbolic math achievement indirectly through specific early math skills (see also Geary & vanMarle, 2016;vanMarle et al, 2018). Also, children who are still developing an understanding of how counting connects to cardinality mapped number words they know onto non-symbolic quantities, and cardinality knowledge predicted children's ability to make these mappings (Batchelor, Keeble, & Gilmore, 2015). However, even this association may be indirect.…”
Section: Ans Task Performance and Specific Early Math Skillsmentioning
confidence: 99%
“…Fuhs, Nesbitt, & O'Rear 591 vanMarle, Chu, Li, and Geary (2014) used a battery of symbolic math tasks and found that it was children's cardinality knowledge that mediated the link between ANS task performance and math achievement, suggesting that children's ANS acuity influences symbolic math achievement indirectly through specific early math skills (see also Geary & vanMarle, 2016;vanMarle et al, 2018). Also, children who are still developing an understanding of how counting connects to cardinality mapped number words they know onto non-symbolic quantities, and cardinality knowledge predicted children's ability to make these mappings (Batchelor, Keeble, & Gilmore, 2015). However, even this association may be indirect.…”
Section: Ans Task Performance and Specific Early Math Skillsmentioning
confidence: 99%
“…Instead, evidence suggests that children who have acquired symbolic skills such as the cardinality principle are more likely to succeed on non-symbolic tasks (Batchelor, Keeble, & Gilmore, 2015; Slusser, Ditta, & Samecka, 2013), leading some to conclude that acquiring symbolic knowledge likely influences non-symbolic skills, rather than the other way around (Merkley & Ansari, 2016). Similarly, relations between ANS acuity and math achievement are mediated by symbolic number knowledge such as Arabic numeral naming and cardinality (Chu, van Marle, & Geary, 2015; see also Merkley & Ansari for a review).…”
Section: Early Numeracy Skills and Their Relation To Mathematical Achmentioning
confidence: 99%
“…Despite the importance of knowing the symbolic system, however, few studies have directly assessed the order in which preschool children (i.e., two-to-four-year olds) make the connections among the three representations (cf. Batchelor, Keeble, & Gilmore, 2015;Benoit, Lehalle, Molina, Tijus, & Jouen, 2013;Odic, Le Corre, & Halberda, 2015;Knudsen et al, 2015). Although most existing evidence is consistent with the view that digit-quantity mapping develops last (Bialystok, 1992;Carey, 2004;Fuson, 1988;Knudsen et al, 2015;Soltësz, Szűcs, & Szűcs, 2010;Zhou & Wang, 2004), only one previous study tested children's knowledge of the mappings in both directions among all three representations.…”
Section: Learning the Mappings Among Quantities Number Words And DImentioning
confidence: 82%
“…An increasing number of studies have been conducted on children's early mapping skills (e.g., Batchelor, Keeble & Gilmore, 2015;Benoit et al, 2013;Knudsen et al, 2015;Mundy & Gilmore, 2009). Researchers have addressed multiple issues such as: a) the relation between mapping skills and early numeracy skills such as counting, cardinality (Batchelor, Keeble, & Gilmore, 2015) and later math skills such as symbolic number comparison (Mundy & Gilmore, 2009); b) whether children learn to map in one direction (e.g., number words to quantities) prior to the other (quantities to number words) (e.g., Odic, LeCorre, & Halberda, 2015); and c) the order of acquisition of the mappings among the three representations of number (e.g., Benoit et al, 2013). Results across studies have been inconsistent.…”
Section: Children's Mapping Skillsmentioning
confidence: 99%
See 1 more Smart Citation